2017
DOI: 10.1016/j.jtho.2017.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Extent of Surgical Resection and Lymph Node Assessment for Clinical Stage I Pulmonary Lepidic Adenocarcinoma: An Analysis of 1991 Patients

Abstract: Background This study examined the association of extent of lung resection, pathologic nodal evaluation, and survival for patients with clinical stage I (cT1-2N0M0) adenocarcinoma with lepidic histology in the National Cancer Database (NCDB). Methods The association between extent of surgical resection and long-term survival for patients in the NCDB with clinical stage I lepidic adenocarcinoma who underwent lobectomy or sublobar resection was evaluated using Kaplan-Meier and Cox proportional hazards regressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…Cox et al showed that in a series of 1991 lipid adenocarcinomas that had either lobectomy or segmentectomy, survival was significantly better after lobectomy, except in the subgroup of SLRs associated with lymph node dissection. The authors concluded that lymph node dissection was essential during segmentectomy ( 35 ). These conclusions are in line with those of Wolf et al and Matioli et al in earlier publications ( 36 , 37 ): segmentectomies have a survival equivalent to that of lobectomies only when lymph node dissection is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Cox et al showed that in a series of 1991 lipid adenocarcinomas that had either lobectomy or segmentectomy, survival was significantly better after lobectomy, except in the subgroup of SLRs associated with lymph node dissection. The authors concluded that lymph node dissection was essential during segmentectomy ( 35 ). These conclusions are in line with those of Wolf et al and Matioli et al in earlier publications ( 36 , 37 ): segmentectomies have a survival equivalent to that of lobectomies only when lymph node dissection is performed.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the conclusions cannot be extrapolated to patients with longer life expectancies. Cox et al 32 examined the association of the extent of lung resection and survival in 1991 patients with IAC and found that limited resection could achieve survival similar to that of lobectomy as long as lymph nodes were examined. However, this study only included patients with lepidic predominant adenocarcinoma and the segmentectomy cohort was too small for subgroup analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the prognosis after treatment by surgical resection, chemotherapy, radiation therapy or combinations is better than in other types. No specific risk factors for this type of lung neoplasia are known [8, 10]. In the described case, no history of a previous lung affection was reported.…”
Section: Discussionmentioning
confidence: 99%